Plant breeding is the food security basis in the Russian Federation - N. P. Goncharov; V. M. Kosolapov (Вавиловский журнал генетики и селекции)
This issue of the Vavilov Journal of Genetics and Breeding is composed of reports of top Russian breeders delivered at the scientific session of the RAS Department of Agricultural Sciences “Scientific support of the efficient development of crop breeding and seed production in the Russian Federation” held in Moscow on December 7, 2020.